Nuevo hallazgo de vertebrados del Plioceno superior en la localidad de Hajnácka I (Eslovaquia del sur) - Sabol, Martin (Coloquios de Paleontología, 2003)
The Hajnácka I site is one of the European paleontological localities dated as Lower Villafranchian, MN 16a unit (Late Pliocene). From its discovery in 19th century, many scientists have dealt with the research of this site. After more than 35 years, the new systematic research started in the second half of 90s of the last century. This new research has yielded a quantity of new data and material,especially paleontological. This article provides the first results on a new site of Villafranchian vertebrates discovered in the territory of the Hajnácka I site.